Discrete-Event Simulation of Aggregation Processes in Batch and Flow Tubular Reactors Based on the Stochastic Lattice Models - Leila Musabekova; Nurlybek Zhumatayev; Nurzhamal Dausheyeva; Madina Jamankarayeva (Chemical Engineering Transactions, 2020)
The novel approach to modeling clusters aggregation which is based on the paradigm of discrete-event simulation (DES) with the help of particles random walk and aggregation on the 3-D stochastic lattices has been applied for describing the aggregation in the heterogeneous poly-dispersive systems. The goal of the work is to generalize the models and results, obtained by the authors earlier for describing aggregation processes, applying to mixed kinetics in batch and flow reactors. The submitted approach allows accounting a different hierarchy of random drift times of particles and aggregation times of clusters of different orders in different areas of the apparatus working volume. The article presents also the principal part of the developed algorithm for the numerical experiment and the main results of the numerical experiment realizing submitted algorithm for wide range of control parameters. As a result, opportunities may open up both to better understanding the nature of scaling in devices with dispersed phase aggregation and for determining the possible ways to optimize the technological regime and apparatus design.